Effect of DNA Damage on the Development of Diabetes Mellitus due toIonizing Radiation Exposure - Al-jameel, Lina; Ghannawi, Lujain; Ehssan, Safaa; Fadhil, Haidar; Amir, Mohammed (ASJ - Academic Science Journal, 2025)
Exposure to ionizing radiation destroys several biological processes by disturbing the membranes of cells and causing damage to DNA, proteins, and mitochondria. Increasing the use of ionizing radiation-based treatment and diagnosis techniques has been associated with the increased chronic diseases among healthcare occupational and patients. However, numerous factors such as duration of exposure, radiation dose, dose rate, the organs of the body exposed, and the person's age impact the ionizing radiation-induced chronic effect. Exposure to ionizing radiation has various harmful effects on healthy tissues; long-term exposure to radiation increases the risk of carcinogenesis and autoimmune diseases such as diabetes. A recent study has also highlighted its potential role in the development of diabetes. This review examines the linkage between radiation-induced DNA damage and diabetes and Explores how radiation can contribute to the emergence and worsening of this chronic metabolic disorder. This review study aims to offer an exhaustive summary of how radiation-induced DNA damage promotes diabetes hazards, highlighting areas for future studies. Also, taking oral antioxidants to protect from radiation-induced DNA damage and mitigate oxidative damage and inflammatory markers after radiation exposure may reduce the incidence of diabetes. Radiation can cause damage to DNA through ionization, which creates free radicals that attack the DNA structure, leading to mutations or breaks in the DNA strands. If this damage occurs in cells involved in glucose regulation or insulin production, it may contribute to the development of diabetes.